Coping With Adolescents Affected by Anorexia Nervosa: The Role of Parental Personality Traits - Monteleone, Alessio Maria; Mereu, Alberta; Cascino, Giammarco; Castiglioni, Maria Chiara; Marchetto, Chiara; Grasso, Melissa; Pontillo, Maria; Pisano, Tiziana; Vicari, Stefano; Zanna, Valeria (Frontiers in Psychology, 2021)
Introduction Anorexia nervosa (AN) promotes psychological distress in caregivers who adopt different coping strategies. Dysfunctional caregiving styles exacerbate further distress in the patient promoting the maintenance of the illness. We aimed to assess the possible contribution of personality traits of caregivers to the adoption of different coping strategies to deal with the affected relative. Methods About 87 adolescents with AN were recruited. Their parents completed the Family Coping Questionnaire for Eating Disorders (FCQ-EDs) and the Temperament and Character Inventory-Revised (TCI-R). Differences between mothers and fathers were assessed through the independent sample t-test. Multivariate regression analyses were run to assess if personality traits, the occurrence of psychiatry conditions in the parents, the marital status, and the duration of the illness predicted parental coping strategies. Results The group of mothers showed higher levels of avoidance and seeking for information coping strategies than the sample of fathers. Lower illness duration predicted higher collusion with the illness in both parents. Harm avoidance, cooperativeness, and self-directedness positively predicted parental coercion, collusion, and seeking for information strategies with some differences between mothers and fathers. Discussion Illness duration and personality traits of parents affect the type of parental coping strategies developed to face AN in adolescents. These variables should be considered in the assessment of families of adolescents with AN and may be addressed to promote more fine-tuned clinical interventions for caregivers.